Pengaruh Cashback, Flash Sale, Tagline â€œGratis Ongkirâ€ Terhadap Impulse Buying Konsumen Generasi Z Pada Shopee (Studi Kasus Mahasiswa Universitas Islam Negeri Sumatera Utara) - Syauqi, Ahmad; Lubis, Fauzi Arif; Atika, Atika (Universitas Labuhanbatu, 2022)
This study aims to determine the effect of Cashback, Flash Sale, and â€œGratis ongkirâ€ Tagline on Impulse Buying Generation Z at Shopee. This type of research uses a quantitative approach. This study uses three independent variables, namely Cashback, Flash Sale, and Tagline â€œGratis ongkirâ€ with one dependent variable, namely Impulse Buying Generation Z at Shopee. After being carried out in the library and in the field, and the preparation of hypotheses, the data in this study were collected through the distribution of questionnaires as research samples with a sampling technique using a Likert scale. Process the data through the SPSS 23.0 program with multiple linear regression analysis techniques. The results of this study can be said that 1) Cashback has a significant effect on Impulse Buying Generation Z at Shopee. With the t count value of the Cashback variable, 4.515 > 1.985 and a significance of 0000 > 0.05. 2) Flash Sale has a significant influence on Generation Z Impulse Buying at Shopee. With the t count value of the Flash Sale variable, namely 2.477 > 1.985 and a significance of 0.015 > 0.05. 3) Free Shipping Tagline has no effect on Impulse Buying Generation Z on Shopee. Because the t count value of the Free Shipping Tagline variable is 1.292 < 1.985 with a significance value of 0.199 > 0.05. 4) Simultaneously variable Cashback, Flash Sale, and Tagline Free Shipping for Impulse Buying Generation Z at Shopee. With a value of Fcount > Ftable 85.669 > 2.71 and a significance of 0.000 < 0.05. This means that there is a significant effect of variables X1, X2, X3 and Y variables together.